SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) TO REDUCE DEPRESSION IN HIV/AIDS SUFFERERS - Erindra Budi Cahyanto; Ika Sumiyarsi Sukamto; Angesti Nugraheni; Mujahidatul Musfiroh; Niken Bayu Argaheni (P3M Universitas Aisyiyah Surakarta, 2021)
There were 90 AIDS sufferers in Surakarta City in 2015 and continued to increase in the following years in line with the increase in sexual behavior outside of marriage. Most of the children who are related to HIV AIDS sufferers are ostracized by their families and the surrounding community and even neglect by their biological families. This causes many problems such as caregivers who are irritable, uncomfortable, depressed, feeling bored, leaving the home, and so on. This community service aims to reduce depression in foster children and caregivers in shelters for AIDS sufferers. The methods used are 1). Program socialization and shared perceptions. 2). Pre test depression score. 3). Spiritual counseling and mentoring with a Spiritual Emotional Freedom Technique (SEFT) approach. 4) Post test for depression score. Twenty HIV / AIDS sufferers are willing to take part in this activity. The result was that the mean score of depression before mentoring was 21.05 (depression) and 17.1 (not depression) after mentoring. Thirteen participants managed to lower their depression score, six participants remained and one person increased. This assistance has an impact on participants to be more enthusiastic in living life.